“Take Nothing but Photos and Leave Nothing but Footprints” (The Tale of a Rooftopper) - Yusuf Kurniawan (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
Urban exploration provides cultural studies researchers with a massive landscape of exploration site. Urban climbing or known as rooftopping is one of the worldwide phenomena performed by urban explorers and usually intended for social media fame. This extreme outdoor activity appeals to many young people although it is life-threatening. Previous research reveals that the number of new rooftoppers kept increasing and many rooftoppers cannot resist rooftopping despite the harsh punishments and heavy sanctions. This article examines the primary motives and principles of a professional Swiss rooftopper who has performed rooftopping for years in several countries. The data were collected through in-depth exclusive interview through WhatsApp text message, voice notes and audio call. Hermeneutics theory by Wilhelm Dilthey is employed to understand how he narrates his rooftopping experiences. Surprisingly, the study reveals that social media fame is not the primary goal but stunning cityscape photos and the ultimate freedom.